Telework: An Innovative Form of Work Organization, a Labor Inclusion Tool and its Legal Regulation in Peru - Culqui Fernandez, Angela (2016)
This article is about the telework, which is an atypical form of work organization, characterized by the use of the information and communication technologies, and the performing of the activities outside the workplace. This type of work can be used as a tool for the inclusion of people into the labor market and the reconciliation between work and family time. Also, we carry out a review and analysis of the current regulations on the subject in Peru.